1989
DOI: 10.1111/j.1524-4725.1989.tb03597.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Multiple Apocrine Hidrocystomas with the Carbon Dioxide (CO2) Laser

Abstract: The apocrine hidrocystoma tends to occur as a solitary facial cystic lesion. We report an unusual patient in whom there were multiple apocrine hidrocystomas scattered over the periorbital region and ears. Although solitary apocrine hidrocystomas are easily treated with excision, we had good results employing carbon dioxide laser vaporization in the treatment of numerous hidrocystomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(7 citation statements)
references
References 19 publications
(28 reference statements)
0
6
0
1
Order By: Relevance
“…This procedure, however, is expensive and requires special training. Bickley et al 13 reported success using a CO 2 laser in a 59‐year‐old woman with multiple hidrocystomas.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure, however, is expensive and requires special training. Bickley et al 13 reported success using a CO 2 laser in a 59‐year‐old woman with multiple hidrocystomas.…”
Section: Discussionmentioning
confidence: 99%
“…Bickley et al, 8 Solitary lesions may cause cosmetic problems, which are usually resolved by surgical removal.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand elimination of multiple lesions is problematic because of their number and location and surgical removal of multiple lesions often results in disfiguring scarring. Lots of methods for their management are described in literature such as electrodessication [46], sclerotherapy [47], blepharoplasty [48], trichloroacetic acid (TCA) [49,50], diode laser [51] and carbon dioxide laser [52][53][54][55].…”
Section: Therapymentioning
confidence: 99%